Examination of the Transdiagnostic Role of Impulsivity in the Development of ADHD and ODD Symptoms in Primary and Secondary School Students - Bruno Barać; Anita Vulić-Prtorić (Education Sciences, 2023)
Attention Deficit/Hyperactivity Disorder (ADHD) and Oppositional Defiant Disorder (ODD) exhibit high comorbidity and variability in terms of dominant comorbid factors across the lifespan. Given the high comorbidity between these disorders, the transdiagnostic factors that may underlie them and could be used to develop effective treatments are of great importance. The focus of this research was on the role of impulsivity as a transdiagnostic factor in the development of ADHD and ODD symptoms in primary and secondary school students. Data were collected from 1161 primary (5th to 8th grade) and secondary (1st to 4th grade) school students (624 females and 537 males). Two models were tested, one for primary and one for secondary school students. Both models propose a significant relationship between ADHD symptoms and ODD, with an emphasis on the relationship between impulsivity and angry/irritable mood. The model for secondary school students does not fit the data, while the model for primary school students fits the data but emphasises attention as the most important factor. These results can be explained by the context of developmental changes and the school environment, both of which influence the stability and intensity of ADHD symptoms.